Curative versus palliative treatments for recurrent hepatocellular carcinoma: a multicentric weighted comparison. Issue 6 (June 2021) - Famularo, Simone; Donadon, Matteo; Cipriani, Federica; Bernasconi, Davide P.; LaBarba, Giuliano; Dominioni, Tommaso; Iaria, Maurizio; Molfino, Sarah; Conci, Simone; Ferrari, Cecilia; Garatti, Marco; Delvecchio, Antonella; et al.
Abstract: Background: Management of recurrence after surgery for hepatocellular carcinoma (rHCC) is still a debate. The aim was to compare the Survival after Recurrence (SAR) of curative (surgery or thermoablation) versus palliative (TACE or Sorafenib) treatments for patients with rHCC. Methods: This is a multicentric Italian study, which collected data between 2007 and 2018 from 16 centers. Selected patients were then divided according to treatment allocation in Curative (CUR) or Palliative (PAL) Group. Inverse Probability Weighting (IPW) was used to weight the groups. Results: 1, 560 patients were evaluated, of which 421 experienced recurrence and were then eligible: 156 in CUR group and 256 in PAL group. Tumor burden and liver function were weighted by IPW, and two pseudo-population were obtained (CUR = 397.5 and PAL = 415.38). SAR rates at 1, 3 and 5 years were respectively 98.3%, 76.7%, 63.8% for CUR and 91.7%, 64.2% and 48.9% for PAL (p = 0.007). Median DFS was 43 months (95%CI = 32-74) for CUR group, while it was 23 months (95%CI = 18-27) for PAL (p = 0.017). Being treated by palliative approach (HR = 1.75; 95%CI = 1.14–2.67; p = 0.01) and having a median size of the recurrent nodule>5 cm (HR = 1.875; 95%CI = 1.22–2.86; p = 0.004) were the only predictors of mortality after recurrence, while time to recurrence was the only protective factor (HR = 0.616; 95%CI = 0.54–0.69; p<0.001). Conclusion: Curative approaches may guarantee long-term survival in case of recurrence.